The Power of Boldness: Ten Master Builders of American Industry Tell Their Success Stories - Elkan Blout
\

Memorial Tributes: Volume 21 - National Academy of Engineering (The National Academies Press, 2017)
This is the 21st Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964. Under the charter of the National Academy of Sciences, the National Academy of Engineering was formed as a parallel organization of outstanding engineers. Members are elected on the basis of significant contributions to engineering theory and practice and to the literature of engineering or on the basis of demonstrated unusual accomplishments in the pioneering of new and developing fields of technology. The National Academies share a responsibility to advise the federal government on matters of science and technology. The expertise and credibility that the National Academy of Engineering brings to that task stem directly from the abilities, interests, and achievements of our members and foreign associates, our colleagues and friends, whose special gifts we remember in this book.

Biographical Memoirs: Volume 80 - National Academy of Sciences (The National Academies Press, 2001)
Biographic Memoirs: Volume 80 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.

The Man Who Would Be Queen: The Science of Gender-Bending and Transsexualism - J. Michael Bailey (The National Academies Press, 2003)
Gay. Straight. Or lying. It's as simple and straightforward as black or white, right? Or is there a gray area, where the definitions of sex and gender become blurred or entirely refocused with the deft and practiced use of a surgeon's knife? For some, the concept of gender 2013 the very idea we have of ourselves as either male or female beings 2013 is neither simple nor straightforward. Written by cutting-edge researcher and sex expert J. Michael Bailey, The Man Who Would Be Queen is a frankly controversial, intensely poignant, and boldly forthright book about sex and gender. Based on his original research, Bailey's book is grounded firmly in science. But as he demonstrates, science doesn't always deliver predictable or even comfortable answers. Indeed, much of what he has to say will be sure to generate as many questions as it does answers. Are gay men genuinely more feminine than other men? And do they really prefer to be hairdressers rather than lumberjacks? Are all male transsexuals women trapped in men's bodies 2013 or are some of them men who are just plain turned on by the idea of becoming a woman? And how much of a role do biology and genetics play in sexual orientation? But while Bailey's science is provocative, it is the portraits of the boys and men who struggle with these questions 2013 and often with anger, fear, and hurt feelings 2013 that will move you. You will meet Danny, an eight-year old boy whose favorite game is playing house and who yearns to dress up as a princess for Halloween. And Martin, an expert makeup artist who was plagued by inner turmoil as a youth but is now openly homosexual and has had many men as sex partners. And Kim, a strikingly sexy transsexual who still has a penis and works as a dancer and a call girl for men who like she-males while she awaits sex reassignment surgery. These and other stories make it clear that there are men 2013 and men who become women 2013 who want only to understand themselves and the society that makes them feel like outsiders. That there are parents, friends, and families that seek answers to confusing and complicated questions. And that there are researchers who hope one day to grasp the very nature of human sexuality. As the striking cover image 2013 a distinctly muscular and obviously male pair of legs posed in a pair of low-heeled pumps 2013 makes clear, the concept of gender, the very idea we have of ourselves as either male or female beings, is neither simple nor straightforward for some.

Biographical Memoirs: Volume 57 - National Academy of Sciences (The National Academies Press, 1987)
This distinguished series contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. A cumulative index for all 57 volumes is now included. For historical and bibliographical purposes, these volumes are worth returning to time and again. Volume 57 includes biographies of: Arthur Francis Buddington, J. George Harrar, Paul Herget, John Dove Isaacs III, Bessel Kok, Otto Krayer, Rebecca Craighill Lancefield, Harold Dwight Lasswell, Jay Laurence Lush, John Howard Mueller, Robert Franklin Pitts, John Robert Raper, Karl Sax, Gerhard Schmidt, Leslie Spier, Hans-Lukas Teuber, and Warren Weaver.

Biographical Memoirs: Volume 90 - National Academy of Sciences (The National Academies Press, 2009)
Biographic Memoirs Volume 90 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.

Biographical Memoirs: Volume 50 - National Academy of Sciences (The National Academies Press, 1979)
Biographic Memoirs: Volume 50 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.

Memorial Tributes: Volume 14 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2011)
This is the fourteenth volume in the series of Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased.

Biographical Memoirs: Volume 65 - National Academy of Sciences (The National Academies Press, 1994)
Biographic Memoirs: Volume 65 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.

Biographical Memoirs: Volume 69 - National Academy of Sciences (The National Academies Press, 1996)
Biographic Memoirs: Volume 69 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.

Biographical Memoirs: Volume 68 - National Academy of Sciences (The National Academies Press, 1995)
Biographic Memoirs: Volume 68 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.

Biographical Memoirs: Volume 76 - National Academy of Sciences (The National Academies Press, 1999)
Biographic Memoirs: Volume 76 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.

Biographical Memoirs: Volume 78 - National Academy of Sciences (The National Academies Press, 2000)
Biographic Memoirs: Volume 78 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.

Biographical Memoirs: Volume 51 - National Academy of Sciences (The National Academies Press, 1980)
Biographic Memoirs: Volume 51 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.

Biographical Memoirs: Volume 44 - National Academy of Sciences (The National Academies Press, 1974)
Biographic Memoirs: Volume 44 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.

Memorial Tributes: Volume 6 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 1993)
This series presents biographies of deceased members of the National Academy of Engineering.

Memorial Tributes: Volume 11 - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2007)
This is the 11th Volume in the series Memorial Tributes compiled by the National Academy of Engineering as a personal remembrance of the lives and outstanding achievements of its members and foreign associates. These volumes are intended to stand as an enduring record of the many contributions of engineers and engineering to the benefit of humankind. In most cases, the authors of the tributes are contemporaries or colleagues who had personal knowledge of the interests and the engineering accomplishments of the deceased. Through its members and foreign associates, the Academy carries out the responsibilities for which it was established in 1964. Under the charter of the National Academy of Sciences, the National Academy of Engineering was formed as a parallel organization of outstanding engineers. Members are elected on the basis of significant contributions to engineering theory and practice and to the literature of engineering or on the basis of demonstrated unusual accomplishments in the pioneering of new and developing fields of technology. The National Academies share a responsibility to advise the federal government on matters of science and technology. The expertise and credibility that the National Academy of Engineering brings to that task stem directly from the abilities, interests, and achievements of our members and foreign associates, our colleagues and friends, whose special gifts we remember in this book.

Biographical Memoirs: Volume 81 - National Academy of Sciences (The National Academies Press, 2002)
Biographic Memoirs Volume 81 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.

Biographical Memoirs: Volume 58 - National Academy of Sciences (The National Academies Press, 1989)
Biographic Memoirs: Volume 58 contains short biographies of deceased members of the National Academy of Sciences.

Biographical Memoirs: Volume 48 - National Academy of Sciences (The National Academies Press, 1976)
Biographic Memoirs: Volume 48 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.